Pro NuGet - Balliauw, Maarten; Decoster, Xavier; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Pro NuGet will give you a solid, practical, understanding of both how to keep your software dependencies under control and what best-practices have been developed within the NuGet community to ensure long-term reliability. Whether you're working entirely with .NET assemblies or also using CSS, HTML and JavaScript files within your applications this book will show you how to manage their requirements smoothly and reliably. As sponsors of the NuGet project Microsoft have led the way in showing how NuGet can be used to great effect; showing how it is now virtually indispensable to anyone working with MVC and the .NET Framework. So don't delay! Learn how to use NuGet effectively today and thank yourself for the time and stress that this powerful free extension will save you. NuGet is an open-source Visual Studio extension that makes it easy to manage libraries, components and configuration files from within your Visual Studio project. As every developer knows, the more complex your application becomes the more chance there is of a dependency conflict arising within the resources upon which you depend. This situation - known as “dependency hell” - used to be an arduous task to unravel and rectify. NuGet changes this situation completely saving you untold time and stress.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems